Peptide-Based TNF-α-Binding Decoy Therapy Mitigates Lipopolysaccharide-Induced Liver Injury in Mice - Chao-Yuan Chang; Hao-Jen Hsu; Jossen Foo; Hung-Jen Shih; Chun-Jen Huang (MDPI AG, 2020)
A peptide named SEM18, possessing structural similarity to the binding site of tumor necrosis factor (TNF)-α to TNF receptor 1 (TNFR1), was designed. We investigated whether the SEM18 peptide can mitigate lipopolysaccharide (LPS)-induced liver injury in mice. Adult male Balb/cJ mice received LPS (15 mg/kg; LPS group) or LPS plus SEM18 (LSEM group). Control groups were run simultaneously. At 2 h after LPS, the first dose of SEM18 (0.3 mg/kg) was administered, followed by three supplemental doses of SEM18 (0.15 mg/kg, every 2 h). At 24 h after LPS, surviving mice were euthanized for analyses. Compared with the LPS group, binding of TNF-α to TNFR1 in liver tissues was significantly lower in the LSEM group (p < 0.001). Plasma concentrations of aspartate transaminase and alanine transaminase, as well as Suzuki's scores (liver damage assessment), wet/dry weight ratios, levels of polymorphonuclear neutrophil infiltration, and levels of mitochondrial injury in liver tissues, of the LSEM group were significantly lower than in the LPS group (all p < 0.05). Levels of necroptosis, pyroptosis, apoptosis, and autophagy upregulation in liver tissues in the LSEM group were also significantly lower than in the LPS group (all p < 0.05). Notably, exogenous TNF-α counteracted these effects of SEM18. SEM18 peptide mitigates LPS-induced liver injury in mice.